2021
DOI: 10.3389/fsurg.2021.655902
|View full text |Cite
|
Sign up to set email alerts
|

Major Amputation Profoundly Increases Mortality in Patients With Diabetic Foot Infection

Abstract: Introduction: An acute diabetic foot infection (DFI) is a serious condition and a leading cause of hospitalization and major amputation in patients with diabetes. Aim of this study was to evaluate the long term survival and risk factors for death and amputation after the DFI requiring hospital treatment.Materials and Methods: A retrospective study included all adult patients hospitalized for DFI treatments during 2010–2014. Overall survival (OS) and amputation free survival (AFS) (without major amputation) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 21 publications
0
31
1
Order By: Relevance
“…Although infection increases the risk of amputation and amputation increases the risk of mortality, [12][13][14][15] we did not find an increased mortality risk in participants with profile 2 infections. Mortality depends on a combination of factors, and type of causative bacteria of DFI, is one of these factors.…”
contrasting
confidence: 78%
See 1 more Smart Citation
“…Although infection increases the risk of amputation and amputation increases the risk of mortality, [12][13][14][15] we did not find an increased mortality risk in participants with profile 2 infections. Mortality depends on a combination of factors, and type of causative bacteria of DFI, is one of these factors.…”
contrasting
confidence: 78%
“…In severe infections (including osteomyelitis), grade 4 of the International Working Group on the Diabetic Foot (IWGDF) diabetic foot infection classification, 77 to 90% of patients will undergo amputation [9][10][11]. Five-year mortality after (major) amputation is as high as 90% [12][13][14][15]. Insight in the association between different bacterial species and outcome is, therefore, of great importance, and might have implications for everyday practice.…”
Section: Introductionmentioning
confidence: 99%
“…Of the 11 studies that analysed the impact of age on the mortality of patients with DFU, eight reported the HR and 95% CI per additional year. 16,18,21,24,30,32,33,35 The pooled HR for every 1-year increase of age was 1.054 (95% CI 1.045-1.063, P < .001). There was mild heterogeneity (I 2 = 33%) (Figure S3).…”
Section: Causes Of Deathmentioning
confidence: 97%
“…Motor neuropathy activates atrophy in the foot muscles, causing osteomyelitis. 60 Sensory neuropathy causes disruption in the skin integrity and provides a route for microbial invasion, resulting in unhealed wounds, which later form chronic ulcers. 61 Autonomic neuropathy results in dysfunction of the sebaceous glands and sweat glands in the foot, leading to Nanoscale Advances Review a predisposition to ssures.…”
Section: Diabetic Neuropathy (Dn)mentioning
confidence: 99%